Design, Construction and Testing of a Model Thermosiphonic Solar Water Heater (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
A thermosiphonic solar water heating system that uses a simple flat plate collector to heat water and in which circulation takes place with natural convention. The system was designed, constructed and tested at Yelwa campus, ATBU Bauchi with latitude 10.330N and longitude 9.830E. The system was designed to heat a total of 15litres of water between 500 and 800 at the worst and best month of the year respectively. The system was designed using weather data of Bauchi state and the resulting parameters of the design was used to construct the system. It was tested between December and January. Two tests were carried out on the system; for the system with ordinary collector, and that with diffusers incorporated within the collector risers. The first system (without diffusers) has an efficiency of 52.6% and was able to generate collector outlet temperature of 610C and water mean temperature of 600C at an average daily solar radiation of 912W/m2. In contrast, the second system (with diffusers) has an efficiency of 58.6% and was able to generate collector temperature of 700C and water mean temperature of 680C at an average daily solar radiation of 913.3W/m2. It was concluded from the results that incorporating diffusers within risers improved the performance of the system by 6.6%.